Haematology: challenges in the 21st century - Jędrzejczak, Wiesław Wiktor (Przewodnik Lekarza/Guide for GPs, 2007)
Haematology is among those medical specialties that on one hand take care of the most seriously ill, and on the other hand are the fastest in introducing achievements of basic sciences to clinical practice. The goal for haematology is to achieve the highest level of cure of both inherited genetically determined disorders, such as haemophilia, and acquired neoplastic disorders. In the article epidemiological, research, diagnostic and therapeutic challenges posed for haematology in the 21st century are discussed as well as challenges that blood disorders may pose to family doctors.